Britannia, Marshall Sons and Co. building - Ghosh, Ayan (2023)
Two statues of Britannia stand aloft on either side of the Marshall Sons and Co. building, one facing Shoorji Vallabhdas Road and the other Shahid Bhagat Singh Marg. Britannia holds a trident (symbol of maritime supremacy) and a shield. She is wearing a Corinthian helmet, and seated at her feet is the British Lion. Britannia is a personification of Great Britain, a symbolic figure that first emerged during the Roman occupation of Britain.